TiO2/silicone encapsulation film for achieving optical performance improvement of chip-on-board packaging LEDs - My Hanh Nguyen Thi; Phung Ton That (Universitas Ahmad Dahlan, 2021)
TiO2 nanoparticle and silicon composite has powerful effect of scattering, thus it is famous in enhancing the scattered light in light-emitting diode (LED) packages. To accomplish higher lighting performance in LED devices, a thin encapsulation layer of TiO2 with high concentration and silicon glue is introduced to complement the main encapsulation one. After conducting experiments, the results present that in the case of the main encapsulation including only silicone, the light extraction efﬁciency (LEE) of COB LEDs increases to 65%. On the other hand, when there is the additional layer of TiO2 and silicone, the improvement of LEE depends on the concentration of TiO2. As this nanoparticle concentration decreases from 0.12 to 0.035 g/cm3, the LEE can be enhanced from 6% to 24%. Moreover, at the average correlated color temperature (CCT) of approximately 8500 K, the layer of TiO2/silicone composite can help to accomplish the reduction of the angular correlated color temperature (CCT) deviation, from 900 to 470 K, within −90° to 90° viewing angle range.